SERS detection of expired tetracycline hydrochloride with an optical fiber nano-probe. Issue 4 (7th January 2015) - Jin, Di; Bai, Yuxue; Chen, Haige; Liu, Shupeng; Chen, Na; Huang, Jing; Huang, Sujuan; Chen, Zhenyi
Abstract : SERS spectra were used to distinguish tetracycline hydrochloride from the expired ones with an optical fiber nano-probe. Abstract : In this paper, we have developed a Raman spectroscopy analytical method for the analysis of tetracycline hydrochloride. Surface enhanced Raman spectroscopy (SERS) was carried out with optical fiber nano-probe coated nanoparticles. Both normal and expired tetracycline hydrochloride were analyzed in direct detection mode and remote detection mode. The results showed that the surface-enhanced Raman spectra could provide chemical information for distinguishing normal drugs from the expired ones. It has been demonstrated that the drug could be analyzed rapidly by SERS with the optical fiber nano-probe.